2011
DOI: 10.1021/jm200293r
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Novel C-Methylated Spermidine Derivatives To Investigate the Regulation of Polyamine Metabolism

Abstract: The polyamines are organic polycations present at millimolar concentrations in eukaryotic cells where they participate in the regulation of vital cellular functions including proliferation and differentiation. Biological evaluation of rationally designed polyamine analogs is one of the cornerstones of polyamine research. Here we have synthesized and characterized novel C-methylated spermidine analogs, that is, 2-methylspermidine, 3-methylspermidine, and 8-methylspermidine. 3-Methylspermidine was found to be me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…The use of metabolically stable polyamine analogues combined with other compounds targeting polyamine metabolism such as DFMO is of great value in studies aiming to elucidate the functions of the individual polyamines [8,25]. However, the functions of the individual polyamines are difficult to assess because they are readily metabolized and complete depletion of one polyamine but not the other is difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of metabolically stable polyamine analogues combined with other compounds targeting polyamine metabolism such as DFMO is of great value in studies aiming to elucidate the functions of the individual polyamines [8,25]. However, the functions of the individual polyamines are difficult to assess because they are readily metabolized and complete depletion of one polyamine but not the other is difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…The optical isomers of (R)/(S)-MeSpd (α-MeSpd) and RR-Me 2 Spm were synthesized as described in [9] and racemic γ -MeSpd as in [8]. (Manassas, VA, U.S.A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used SC instead of aminoguanidine (AG), another widely used serum amine oxidase inhibitor, because we found that AG treatment alone inhibits DHS and retards cell growth 15 . Our previous studies indicated that racemic 1-, 2-, and 3-MeSpd were not cytotoxic in the absence of serum amine oxidase inhibitor, while Spd and rac-8-MeSpd were 16 . Thus, racemic 1-, 2-and 3-MeSpd were not considered to be degraded by the serum amine oxidases to cytotoxic aldehydes 16 .…”
Section: Resultsmentioning
confidence: 94%
“…[25]. A standard assay mixture contained 100 mM Tris-HCl, pH 7.8, 1 mM semicarbazide, 5 mM EDTA, 3 mM 8-MeSpd [26], and 50 nCi (50-60 mCi/mmol) of 14 C-acetyl-CoA (Moravek Inc.) in a total volume of 100 μl. 8-MeSpd has higher affinity for SAT1 in comparison to its natural substrate spermidine (K m 78 ± 3 µM and V max of 7.35 ± 0.10 µmol/min/mg vs. K m 151 ± 15 µM and V max of 4.28 ± 0.13 µmol/min/mg).…”
Section: Analysis Of Sat1 Activitymentioning
confidence: 99%